Pelatihan Pengelolaan Organisasi Pada Lembaga Swadaya Masyarakat New Generation Club (NGC) Di Masa Pandemi Covid-19 - Muhammad Yahrif; Hasnani; Najwa Lahmady (Yayasan Habiburrahman Jamalu Bina Ummat, 2022)
Organizational management is one of the things that is very important to achieve the goals, vision, and mission of the organization. Good organizational management will make the organization run well. But the Covid-19 pandemic had caused changes in the organizational structure. This had an impact on several community organizations not working well. One of the community organizations that had an impact was the NGC New Generation Club (NGC). NGC administrators found it difficult to carry out all activities that had been planned to be online activities or restrictions with certain permits. Seeing this, it is necessary to have organizational management training at the New Generation Club (NGC) non-governmental organization after the pandemic. This community service used online training methods. It is hoped that with this organizational management training, the NGC NGC administrators are able to carry out all activities even though they are in online form so that the organization can run well.